Integration of Financial and ESG Performance Indicators to Measure and Evaluate Egyptian Insurance Companies Performance - AbdelNour, Haidy Anwer Saeed; Elfaky, Alsebai Mohamed Alsebai (Journal of Applied Business and Economics, 2024)
This study aims to evaluate the performance of Egyptian insurance companies through the integration of financial and non-financial performance indicators through the dimensions of sustainable development as a mediator variable. The study relied on Allianz Egypt property and liability insurance company data from 2012 to 2021, and the Monte Carlo simulation method was used based on the Mathcad program. This study used structural Equations Modeling via AMOS program to extract the direct and indirect effect through path analysis. The results showed that each environmental dimension, social dimension, and governance dimension plays a mediator role in the relationship between solvency, liquidity, credit, activity, underwriting profitability, and both market share and investment profitability. Our research contributes to the literature of achieving sustainable development in the insurance sector, to keep pace with global developments. This paper presents evidence of the relationship between integrating ESG indicators into insurance companies’ performance and achieving an additional competitive advantage.